APPROACHES TO ECOLOGICAL STATUS ASSESSMENT OF URBAN TERRITORIES - Trubina, Lyudmila; Nikolaeva, Olga; Moskvin, Victor (Revista Inclusiones, 2020)
Urban territories are marked by a high level of environmental pollution. A comprehensive analysis of pollution sources and pollutant spreading, determined by the natural conditions of the territory and the urban infrastructure, is needed to assess the environmental situation of the city. This approach regards the urban environmental situation as a dynamic medium, changing in time and space. This study aims to substantiate the approach to the integrated ecological status assessment of urban territories, based on geoinformation analysis and 3D cartographic modeling of pollutant distribution in the urban environment. The paper proposes the principles of integrated environmental assessment, including analysis of both the degree of pollution and the processes of pollutant distribution. The experimental analysis of the ecological status was performed in Novosibirsk, Russia. A digital terrain model, a digital model of terrain features that have an adverse impact on the environmental situation, and an environmental database were created. The city was zoned based on the composite indicator of the hazard level. Pollutant fluxes from the anthropogenic objects, posing environmental hazard, was 3D-modeled.